Review of Shape and Color on Poleng Motifs in Bali - Arya Pageh Wibawa; Imam Santosa; Setiawan Sabana; Achmad Haldani Destiarmand (Mudra Jurnal Seni Budaya, 2023)
In the beginning, the poleng motif was a sacred motif by the Balinese people. The poleng motif has a meaning as a form of petition and protection to God Almighty in His form and manifestation as creator, preserver, and harmonizing to achieve a happy and prosperous life. Another meaning is as a form to neutralize and restore balance from dark forces to help achieve the perfection of life. In its application as a motif wrapped around sacred objects, the poleng motif has the meaning of a repellent to strengthen and as a place of worship of God in His manifestation as a guardian. In subsequent developments due to tourism with increasing local and foreign tourist visits, the poleng motif has functioned as a decoration. This shift certainly leads to a reinterpretation of the meaning of the poleng motif in Bali. This study aims to get a new meaning for the poleng motif in Bali. To get this new meaning, a qualitative methodology is used based on the theoretical basis of Panofsky's iconology which emphasizes the study of visual analysis. The study carried out resulted in new findings in the form of a new meaning for the poleng motif. Based on the analysis, it was found that there was a shift in meaning from sacred to profane with the new meaning of the poleng motif being cultural communication. The form of communication created is a self-image product that reflects Balinese cultural identity. Local cultural identity is used to introduce Balinese culture.